Tetanus, Diphtheria, and Acellular Pertussis and Influenza Vaccinations among Women With a Live Birth, Internet Panel Survey, 2017-2018. (February 2020) - Murthy, Neil Chandra; Black, Carla; Kahn, Katherine E; Ding, Helen; Ball, Sarah; Fink, Rebecca V; Devlin, Rebecca; D'Angelo, Denise; Fiebelkorn, Amy Parker
Objectives: Pregnant women are at increased risk of complications from influenza, and infants are at increased risk of pertussis. Maternal influenza and Tdap (tetanus, diphtheria, and acellular pertussis) vaccination can reduce risk of these infections and related complications. Our objective was to estimate vaccination coverage with influenza and Tdap vaccines during pregnancy among women with a recent live birth. Methods: An opt-in Internet panel survey was conducted from March 28 to April 10, 2018 among pregnant and recently pregnant women. Respondents with a live birth from August 1, 2017 through the date in which the participant completed the survey were included in the analysis. Receipt of influenza vaccination since July 1, 2017 and Tdap vaccination during pregnancy were assessed by sociodemographic characteristics, receipt of a health care provider (HCP) recommendation and/or offer of vaccination, and vaccination-related knowledge, attitudes, and beliefs. Results: Less than a third (30.3%) of women with a live birth were unvaccinated during their pregnancy with both Tdap and influenza vaccines. Almost a third (32.8%) of the women reported being vaccinated with both vaccines. The majority (73.0%) of women reported receiving an HCP recommendation for both vaccines, and 54.2% of women were offered both vaccines by an HCP. Reasons for nonvaccination included negative attitudes toward influenza vaccine and lack of awareness about Tdap vaccination during pregnancy. Conclusions: Maternal Tdap and influenza vaccinations can prevent morbidity and mortality among infants and their mothers, yet many pregnant women are unvaccinated with either Tdap or influenza vaccines. Clinic-based education, along with interventions, such as standing orders and provider reminders, are strategies to increase maternal vaccination.